2016
DOI: 10.1186/s40560-016-0187-7
|View full text |Cite
|
Sign up to set email alerts
|

Augmented renal clearance in Japanese intensive care unit patients: a prospective study

Abstract: BackgroundAugmented renal clearance (ARC) of circulating solutes and drugs has been recently often reported in intensive care unit (ICU) patients. However, only few studies on ARC have been reported in Japan. The aims of this pilot study were to determine the prevalence and risk factors for ARC in Japanese ICU patients with normal serum creatinine levels and to evaluate the association between ARC and estimated glomerular filtration rate (eGFR) calculated using the Japanese equation.MethodsWe conducted a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…In a previous trial of febrile neutropenic patients, we observed that 31% of the study cohort exhibited ARC. This is comparable to other reports for intensive care unit (ICU) patients: 33% by Ruiz et al (26), 38.7% by Kawano et al (27), and 28% by Campassi et al (28). A higher incidence in ICU patients was also reported by other authors, e.g., 55.8% (29) and 65.1% (30).…”
Section: Discussionsupporting
confidence: 88%
“…In a previous trial of febrile neutropenic patients, we observed that 31% of the study cohort exhibited ARC. This is comparable to other reports for intensive care unit (ICU) patients: 33% by Ruiz et al (26), 38.7% by Kawano et al (27), and 28% by Campassi et al (28). A higher incidence in ICU patients was also reported by other authors, e.g., 55.8% (29) and 65.1% (30).…”
Section: Discussionsupporting
confidence: 88%
“…Instead, we used the eGFR values which were calculated by a Japanese equation for evaluating ARC. This Japanese equation has been reported to underestimate the GFR in ICU settings [10]. In addition, other commonly used formulas (such as CG, MDRD, and CKD-EPI) for eGFR worldwide have also been shown to underestimate the actual measured CrCl in ARC patients [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese eGFR equation(J-eGFR) [17] For males: eGFR (mL/min) = 194 ×SCr -1.094 ×age -0.287 For females: eGFR (mL/min) = 194 ×SCr -1.094 ×age -0.287 ×0.739…”
Section: Chronic Kidney Disease Epidemiology Collaboration Equation Fmentioning
confidence: 99%